FORMULASI EPISTEMOLOGI FRANCIS BACON DAN RENE DESCARTES DALAM TRADISI KEILMUAN ISLAM - ach - Tijani (Jurnal Al-Hikmah: Jurnal Dakwah, 2018)
Islam and the West are two sivilizations which that seem to be on two sides facing each other. The West represents the progress while Islam represents the lagging. Even though, these symptoms cannot be categorized in black and white, but the Western power in dominating science, technology and politics is an indicator of progress, while Islam is in a stagnant line following the control of Western domination. This study starts from the awareness in rethinking on the epistemological context of science in Islam and at the same time comparing it with the initial starting point of progress in the West by two pioneers of Western philosophers, Francis Bacon and Rene Descartes. Through a philosophical study it was found that the scientific epistemology of Islam must shift from mere study of the text (bayani), proof of the text (burhani) and deep appreciation of the text (irfani) to cosmological studies as objects of knowledge through empirical phenomena and potential awareness of ratio. Islam dan Barat adalah dua peradaban yang seakan berada pada dua sisi yang berhadap-hadapan. Barat merepresentasikan kemajuan sementara Islam merepresentasikan ketertinggalan. Gejala tersebut walau tidak dapat dikategorikan secara hitam-putih, namun kedigdayaan Barat dalam mendominasi ilmu pengetahuan, teknologi dan politik setidaknya menjadi indikator dari sebuah kemajuan. Kajian ini bertolak dari kesadaran tersebut dalam melihat kembali konteks epistemologis keilmuan dalam Islam dan sekaligus membandingkannya dengan titik tolak awal kemajuan di Barat oleh dua pelopor filsuf Barat yaitu Francis Bacon dan Rene Descartes. Melalui telaah filosofis ditemukan bahwa epistemologi keilmuan Islam harus bergeser dari sekedar telaah teks (bayani), pembuktian teks (burhani) dan pengahayatan teks (‘irfani) pada kajian kosmologis sebagai obyek pengetahuanmelalui fenomena empiris dan potensi kesadaran rasio. Kata Kunci: Ilmu, epistemologi, teks, konteks